Strategi Inovatif Dan Tantangan Yang Dihadapi Dalam Pembelajaran Kalam Bahasa Arab - Fardiya, Yuma; Taufik, Taufik (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2024)
To build the success of a country, education is needed as the main foundation, in this developing era, innovation and adaptation are needed according to the needs of the times. This research is expected to improve the quality of kalam learning in Arabic and overcome the challenges that exist in the modern era so that it can meet the needs of students. This research uses a qualitative approach with library research with the main data from various relevant literature. The results showed that innovative strategies for learning kalam can overcome some of the challenges faced today by using technology in learning and interactive methods, this strategy is expected to increase student interest and understanding in learning Arabic kalam